Magnetic characteristics of nanocrystalline multiferroic BiFeO3 at low temperatures - Vijayanand, S.; Mahajan, Mangesh B.; Potdar, H. S.; Joy, Pattayil Alias (Physical Review B, 2009)
The magnetic characteristics of nanocrystalline BiFeO3 with average crystallite sizes of similar to 50 and similar to 100 nm are evaluated by studying the temperature and field dependence of magnetization at low temperatures. Different properties such as magnetization, coercivity, and remanence show evidence for changes in the magnetic properties associated with the phase transitions at low temperatures, reported from Raman studies. Detailed field-cooled and zero-field-cooled magnetization measurements show that the likely origin of the changes in the magnetic characteristics is from the changes in the domain structure.
Keywords: bismuth compounds; coercive force; crystallites; magnetic domains; magnetic transitions; Multiferroics; Nanostructured materials; Raman spectra; remanence

Magnetic studies of SiO2 coated CoFe2O4 nanoparticles - Limaye, M.V. (Journal of Magnetism and Magnetic Materials, 2017)
Oleic acid capped CoFe2O4 nanoparticles which exhibit a high coercivity of ∼9.47 kOe at room temperature were coated with a robust coating of SiO2. We have used chemical synthesis method to obtain SiO2 coated CoFe2O4 nanoparticles with different weight percentages of CoFe2O4 in SiO2 (1.5, 3.1 and 4.8 wt.%). The morphological investigation of the coated nanoparticles by transmission electron microscopy shows that the particles are spherical with average size ∼160 nm. Infrared spectroscopy reveals that oleic acid capping on the surface of CoFe2O4 nanoparticles is retained after silica coating process. The complete coating of SiO2 on CoFe2O4 nanoparticles is confirmed by X-ray photoelectron spectroscopy as there is no signature of cobalt or iron ions on the surface. Magnetic measurements show that coercivity of SiO2 coated CoFe2O4 particles remains more or less unaffected as in CoFe2O4 nanoparticles at room temperature. In addition, the temperature dependent magnetic measurements show that at 5 K the CoFe2O4 and SiO2 coated 1.5 wt.% CoFe2O4 samples exhibit a very high value of coercivity (∼20 kOe) which is more than twice as compared to room temperature coercivity value (∼9.47 kOe). We conclude that silica coating in our study does not significantly affect the coercivity of CoFe2O4 nanoparticles.
Keywords: Coatings; coercive force; High Resolution Transmission Elctron Microscopy; infrared spectroscopy; Magnetic materials